Prinsip-Prinsip Al-Qur’an tentang Norma-Norma Ekonomi - Ade Jamarudin (Institut Ilmu Keislaman Annuqayah, 2017)
This study aims to reveal the principles of the Qur'an about economic norms that play an important role in creating balance and equality of life for society as a whole. Based on the principles of the Qur'an, all activities and economic transactions can be controlled on the basis of the purpose of Islamic teachings. This research uses literature study to find out normatively what is the basic principles of the Qur'an about economic norms and ethics that became the main foundation in carrying out all business or business activities. This study shows that the economic norm is the main prerequisite to create balance in building the economic system based on populist economy. As for the principles of the Qur'an about economic norms or rules is not separated values of unity, honesty, balance, justice, and responsibility. As the main source, the Qur'an contains the ethics and norms that govern all human activities in meeting their individual needs, especially economic activity. So the principles of the Qur'an about the economic norms as practiced by the Prophet must be revived in the midst of the hegemony of the capitalist economic system that controls the world economy.